2012
DOI: 10.5923/j.scit.20120204.01
|View full text |Cite
|
Sign up to set email alerts
|

Development of Arginine Based Monopeptides as Cationic Surfactants from Pure Amino Acid

Abstract: A mino acid-based surfactants constitute a class of cationic surfactants with excellent surface p roperties, wide biological activ ity, low potential to xicity. Essential structural factors for their antimicrobial activity include both the length of the fatty residue and the presence of the protonated guanidine function. These features and the use of natural raw materials such as Arginine and fatty acids for their synthesis, make them interesting candidates as preservatives and antiseptics in pharmaceutical, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The biocidal effect of the synthesized surfactants against the environmental sulfidogenic-bacteria was evaluated by determine the minimum inhibitory concentration (MIC). The MIC is defined as the lowest concentration of antimicrobial agent that inhibits the development of visible microorganism growth [20]. Samples were taken from the bulk phase of reactor A after 5 days cultivation and tested for viable bacterial counts using the most probable number (MPN) method [21].…”
Section: Reactors Setup and Evaluation Of Sulfidogenic Activitymentioning
confidence: 99%
“…The biocidal effect of the synthesized surfactants against the environmental sulfidogenic-bacteria was evaluated by determine the minimum inhibitory concentration (MIC). The MIC is defined as the lowest concentration of antimicrobial agent that inhibits the development of visible microorganism growth [20]. Samples were taken from the bulk phase of reactor A after 5 days cultivation and tested for viable bacterial counts using the most probable number (MPN) method [21].…”
Section: Reactors Setup and Evaluation Of Sulfidogenic Activitymentioning
confidence: 99%
“…The exchange capacity of ion exchange resins was experimentally determined by the standard method [17] using sodium nitrate and titrating against standard silver nitrate solution. Ion exchange resins (0.500 g) in chloride form were equilibrated with iodide ion solution of different concentrations at a constant temperature of 30.0 °C for 3 h. From the results of kinetics study reported earlier [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]; it was observed that this duration was adequate to attain the ion exchange equilibrium. After 3 h, the iodide ion solutions in equilibrium with ion exchange resins in chloride form were analyzed for their chloride and iodide ion concentrations by …”
Section: Methodsmentioning
confidence: 99%
“…The exchange capacity of ion exchange resins was experimentally determined by the standard method [17] using sodium nitrate and titrating against standard silver nitrate solution. Ion exchange resins (0.500 g) in chloride form were equilibrated with iodide ion solution of different concentrations at a constant temperature of 30.0 °C for 3 h. From the results of kinetics study reported earlier [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]; it was observed that this duration was adequate to attain the ion exchange equilibrium. After 3 h, the iodide ion solutions in equilibrium with ion exchange resins in chloride form were analyzed for their chloride and iodide ion concentrations by…”
Section: Methodsmentioning
confidence: 99%